Modern concepts on the physiology of the kidney - Newman, Elliot V. (1948)
The study of the physiology of the kidney may be, in my opición of great interest for clinical and aid in the understanding and treatment of patients with conditions that compromise, directly or indirectly to the kidney. Most of my dissertation, however, depart from any immediate application to clinical practice, but I hope that may be of some value for understanding nosological processes.